Decellularization and sterilization of porcine urinary bladder matrix for tissue engineering in the lower urinary tract. (March 2008) - Rosario, Derek J; Reilly, Gwendolen C; Ali Salah, Emadaldeen; Glover, Maggie; Bullock, Anthony J; MacNeil, Sheila
Background: Several synthetic and natural matrices have been described for tissue engineering of bladder but there is little information on the effects of processing on their subsequent mechanical performance or interaction with human cells.Aim: Our aim was to assess the effects of delamination, decellularization and sterilization on the mechanical properties of porcine urinary bladder matrix (UBM) and to then assess the ability of the UBM to act as a scaffold for reconstruction with human bladder cells.Methods: A total of 20 porcine bladders were assessed before and after mechanical delamination and four porcine bladders were followed at every stage through a comparison of several decellularization and terminal sterilization methodologies examining histological and mechanical characteristics. The sterile UBM was seeded with normal human urothelial and bladder stromal cells either as a simultaneous coculture, or with stromal cells followed by urothelial cells.Results: Mechanical delamination, physical rinsing of the resulting bladder stroma in hypotonic buffer, 0.1% sodium dodecyl sulfate solution and 0.1% peracetic acid resulted in an UBM with acceptable mechanical properties capable of supporting urothelial and bladder stromal cells. Terminal sterilization with ethylene oxide resulted in considerable stiffening of the matrix simultaneous coculture and layered seeding of scaffolds with stromal cells followed by epithelial cells gave similar results with good initial urothelial attachment (followed by loss of cells later) and slow stromal cell penetration.Conclusion: We describe a decellularized sterilized porcine UBM with acceptable mechanical properties that shows promise as a scaffold for producing an in vitro tissue-engineered bladder patch material for lower urinary tract reconstruction. Future work now needs to focus on the conditions for achieving secure epithelial attachment.